The European Hot Spot of B[a]P and PM2.5 Exposure—The Ostrava Region, Czech Republic: Health Research Results. (9th May 2013) - Sram, Radim J.; Dostal, Miroslav; Libalova, Helena; Rossner, Pavel; Rossnerova, Andrea; Svecova, Vlasta; Topinka, Jan; Bartonova, Alena
Abstract : The Ostrava Region in the Czech Republic is a heavily polluted industrial area. Concentrations of PM10, PM2.5, and benzo[a]pyrene (B[a]P) significantly exceed limit values. To investigate the impact of these levels on human health, epidemiological, molecular epidemiology, and in vitro studies were done in 2008–2011. Morbidity of children was followed in 10 pediatric districts. In the most polluted district, children suffered higher incidence of acute respiratory diseases in the first year of life, and higher prevalence of asthma bronchiale. Gene expression was studied in children from Ostrava and from a control rural area. Genes specific to asthma bronchiale differed, suggesting a different molecular phenotype in children in the polluted region compared to children in the control area. A molecular epidemiology study showed adverse effect of the Ostrava exposures, but also an increased expression of XRCC5, which probably protects these exposed subjects against the degree of genetic damage that would otherwise be expected. In vitro studies clearly related concentration of B[a]P from PM2.5 extracts to induced PAH-DNA adducts. These studies clearly demonstrate that under the present local environmental conditions, the health of the population is severely impaired and will likely remain so for a significant period of time.